A CASE STUDY OF SPONTANEOUS DIABETES MELLITUS IN GOAT - SURISETTI, RAVI BABU; RAO, ADARI ARJUNA APPA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Diabetes is a metabolic condition that has wide-ranging effects on numerous bodily processes. The majority of research on diabetes in ruminants was conducted on animals in which diabetes was artificially caused. Conversely, other domestic species rarely have the clinical condition of diabetes described in them (cattle, small ruminants). Numerous factors, including reduced insulin synthesis, decreased insulin sensitivity in target cells and organs, an excess of other hormones and medications, or different combinations of these factors, may contribute to the sneaky development of diabetes. It was discovered that ruminants occasionally experienced uncommon spontaneous diabetic episodes in which their blood plasma glucose levels increased. High blood glucose levels were noticed in goat this case study, which was recorded, and an effort was made to determine cause of this condition.